PC.54 A rare presentation of Malassezia fungaemia with liver abscess in preterm neonate. (9th June 2014) - Abraham, D; Gray, J; Rasiah, SV
Abstract : We present a 24 week old male infant weighing 758 gram with significant surfactant deficient respirtory distress. He was extubated on day 19 and remained on BIPAP until he was reintubated on day 28 following suspected infection. He was on prophylactic fluconazole from birth. While on Meropenem for enterococcal infection, Amphotericin was started on day 28 due to suspected fungal infection following a rising CRP and fall in platelet count. This was confirmed on Day 30. On day 32, an abdominal ultrasound showed multiple echogenic lesions within hepatic parenchyma suggesting fungal lesions. The blood culture confirmed Malassezia pachydermatis fungal infection. Voriconazole was started on advice from Microbiologist. Repeat abdominal scan in two weeks showed significant resolution of hepatic lesions. He remained ventilated following this episode of fungal infection with a progressively increasing severe post-haemorrhagic ventricular dilatation. Following a multidisciplinary team meeting and discussion with parents, he was redirected to palliative care. Candida species is the most common pathogen causing invasive fungal infection in very low birthweight (VLBW) infants. Malassezia sp. remains underdiagnosed, as it does not routinely grow in usual cultures and requires lipid-supplemented media. The national prospective surveillance study on invasive fungal infection in VLBW infants in UK 2003–04 lists the sites of isolation of fungi as pneumonia, renal fungal balls, meningitis, peritonitis, skin abscess, osteomyelitis, endocarditis and opthalmitis. Liver abscess was not reported in this series. This case highlights the importance of maintaining high index of suspicion to diagnose invasive fungal infections in VLBW infants. Reference: Clerihew L, Lamagni TL, Brocklehurst P, and McGuire W. Invasive fungal infection in very low birthweight infants: national prospective surveillance study. Archives of Disease in Childhood . Fetal and neonatal edition, 2006;91(3):F188–92. doi:10.1136/adc.2005.082024